Faktor-faktor yang Mempengaruhi Preeklampsia pada Kehamilan Primigravida - Inggit Primadevi; Rike Indriani (Majalah Kesehatan Indonesia, 2022)
Preeclampsia is a multi-systemic disorder that occurs in pregnancy which is characterized by hypertension and edema accompanied by urine protein. The research objective was to find out whether preeclampsia on primigravida was related to age, history of ANC, heredity factors, gameli and comorbidities at Batin Mangunang Hospital in 2020. The type of research was quantity with a cross sectional design, the population in this research were all mothers who gave birth with preeclampsia at Batin Mangunan Hospital in 2020 with a case sample of 70 patients, the analysis used Univariate and Bivariate by using the chi square test. From the results of this research, the results of the analysis of age with P Value 0.026 History of ANC P Value with 0.781 Hereditary factors with Value 0.030 Comorbidities with P Value 0.017 gameli with P value 01.0 it can be concluded that there is a significant correlation between preeclampsia on primigravida with age factor, Hereditary comorbidities and there is no significant correlation history of ANC and gameli. The suggestions given are expected, especially for health workers to provide continuous counselling to provide counselling, carry out early detection by carrying out supporting tests such as hemoglobin and urine protein examination and for officers health care in hospitals to improve the ability to treat preeclampsia.   Abstrak: Preeklampsia adalah kelaianan Multi sistemik yang terjadi pada kehamilan yang di tandai dengan adanya hipertensi dan odema diseratai protein urine. Tujuan Penelitian ini untuk Diketahuinya apakah preeklampsia pada primigravida berhubungan dengan usia, Riwayat ANC, Faktor Keturunan, Kehamilan Ganda dan penyakit Penyerta Di RSUD Batin Mangunang tahun 2020. Jenis penelitian Kuantitas dengan rancangan cross sectional, populasi pada penelitian ini adalah seluruh ibu bersalin dengan preeklampsia di tahun 2020 Rumah Sakit Batin Mangunang dengan sampel kasus 70 pasien, analis yang digunakan  Univariat dan Bivariat, dengan menggunakan Uji chi square. Dari hasil Penelitian ini diperoleh hasil analisa Usia dengan P Value 0,026 Riwayat ANC P Value dengan 0,781 Faktor keturunan dengan Value 0,030 Penyakit penyerta dengan P Value 0,017 Gameli dengan  P value 01,0 maka dapat disimpulkan ada hubungan yang signifikan antara preeklampsia pada primigravida dengan faktor Usia, Faktor Keturunan Penyakit Penyerta dan tidak ada hubungan yang signifikan Riwayat ANC dan  Kehamilan ganda. Saran yang disampaikan diharapkan khususnya bagi petugas kesehatan agar memberikan penyuluhan terus menerus untuk memberikan penyuluhan, melakukan deteksi dini dengan melakukan pemerisaan penunjang seperti hemoglobin dan pemeriksan protein urine dan untuk petugas kesehatan di rumah sakit tingkatkan kemampuan penanganan preeklampsia.